Efficacy and safety of sacubitril-valsartan in Maintenance Hemodialysis patients with hypertension:A retrospective study - Lili Jiang; Jing Ran; Yu Zhu; Lupin Pan; Bayi Yang; Xue Ran; Ying Ran; Hejun Ding; Jurong Yang; Shaofa Wu (PLoS ONE, 2025)
Background Hypertension is associated with elevated mortality rates among individuals on maintenance hemodialysis (MHD). However, there is limited information regarding the efficacy and safety of sacubitril-valsartan (SV) in MHD patients suffering from hypertension. Consequently, this study aims to evaluate the efficacy and safety of SV in this specific patient population. Methods We retrospectively reviewed the data of MHD patients with hypertension who were receiving SV treatment at our hospital from January 1, 2023 to June 30, 2024. The SV dose ranged from 50 mg twice daily to 200 mg twice daily. Blood pressure measurements were compared at baseline and during follow-up intervals to assess therapeutic efficacy. Safety evaluations included comprehensive monitoring of treatment-emergent adverse events throughout the observation period. Results A total of 64 MHD patients hypertension (mean age = 54.11 years; male proportion = 73.4%) were ultimately included in the study. After three months of treatment with SV, the mean reductions in systolic blood pressure, diastolic blood pressure, and pulse pressure were 21.06 ± 15.82 mmHg (P < 0.001), 8.41 ± 13.09 mmHg (P < 0.001), and 12.65 ± 13.17 mmHg (P < 0.001), respectively. With respect to safety, new-onset intradialytic hypotension was observed in three patients. The study also included twelve patients with hyperkalemia. Importantly, no patients reported experiencing cough, angioedema, or abnormal liver biochemistry. Among the 64 subjects, none required a dose reduction or discontinuation of SV due to these adverse effects. Conclusions In MHD patients with hypertension, SV demonstrates a preliminary ability to lower blood pressure and appears safe. Further prospective randomized studies are warranted to validate our findings.